PERANCANGAN PEMBELAJARAN TEMATIK PENGARUH HUJAN TERHADAP LAJU INFILTRASI ASPEK FISIS DALAM EKOSISTEM TANAMAN SALAK - Gratsia Manuho; Jeane V. Tumangkeng; Theresje Mandang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
Learning in nature is a real form of the educational process. Siau Tagulandang Archipelago Regency which is an area of salak plantation forest that is widely cultivated by the community, but this has an impact on the absence of learning activities, especially regarding physics in the area. So, to realize the process of learning activities in the area of salak plants, an expolarative research was carried out with the aim of identifying the ecosystem and the interactions that occurred and analyzing the effect of the frequency of rain on the infiltration rate. That infiltration is the flow of water into the soil through the soil surface. Infiltration (infiltration rate and capacity) is strongly influenced by various variables, including soil type, slope, density and type of vegetation, soil water content, and rainfall intensity. This research is an expolarative research that emphasizes how students can see the facts/phenomenon they see with the concept of physics. The rate of infiltration and the infiltration capacity of the soil decreases in direct proportion to the increase in the frequency of rain, the more the frequency of rain, the smaller the infiltration that occurs at the same level of rain intensity